Cognitive Function and Heart Failure: The Role of the Adrenergic System - D. Femminella, Grazia; Candido, Ciro; Conte, Maddalena; Provenzano, Sandra; Rengo, Carlo; Coscioni, Enrico; Ferrara, Nicola (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2016)
Background: Heart Failure (HF) and cognitive impairment (CI) represent two high incident diseases worldwide, with extremely elevated mortality and morbidity rates. Their prevalence is expected to further increase in the next years due to the aging population, thus they pose enormous clinical, social and economic challenges. Sympathetic nervous system hyperactivity is known to play a pivotal role in HF pathophysiology and progression. In fact, increased cardiac and circulating catecholamine levels are responsible for several molecular and structural abnormalities with detrimental effects on the failing heart. The proof of this latter concept is represented by the clinical success of β-Blocker therapy that is able to attenuate HF-related morbidity and mortality. Recently, adrenergic system alterations have been implied also in the pathogenesis of CI and dementia opening the window for new fascinating and promising therapeutic opportunities. Objective: Assess the state of the art on the relationship between cognitive impairment and heart failure. Method: In the present manuscript, we propose an updated review of literature and patent on the role of sympathetic nervous system derangement in the pathogenesis of HF and CI. Conclusion: We have discussed recent findings allowing the identification of new molecular targets that hopefully will contribute to the generation of effective therapeutic strategies for HF and dementia. In this article, the patents US20100048479, US7060871, WO2006052857, US7351401, US5721243, WO1994009155, US5449604, WO1999058981, US5985581, EP2319511, EP2377534, EP2650303, WO2006004939, WO2010132128 and EP1779858 are summarized.
Keywords: dementia